WAYS TO INCREASE THE ENERGY EFFICIENCY OF NEW, RECONSTRUCTED AND EXISTING BUILDINGS. - Akhmedov Islombek; Umarov Isroil; B.Sharopov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. This article discusses the development and implementation of a scientifically based legislative, regulatory and methodological framework for the design and construction, as well as the operation of buildings and structures, aimed at increasing the energy efficiency of buildings under construction